Production technology and trade of 4th–1st centuries BC cooking jars from the Pontine Region in southern Lazio (Italy) - Borgers, Barbara; Verhagen, Filmo; Tol, Gijs; de Haas, Tymon (Rei Cretariae Romanae Fautorum Acta, 2024)
Previous research conducted as part of the Pontine Region Project in southern Lazio has indicated that 4th–1st centuries BC cooking jars from the low-lying central part of this region were obtained through regional and supra-regional trade networks. Building upon this, the present paper examined cooking jars from three micro-regions within the Pontine region, i.e., the coastal area, the central plain and the foothills of the Lepini Mountains respectively, to reconstruct their production technology and trade networks. The results indicate that the cooking jars from the three micro-regions occur in six compositions; four seem to have been imported from production areas either from the north (e.g., Rome and Tiber Valley) or from the south (e.g., Bay of Naples), while two compositions might have been produced in the Pontine region. Possible changes in the relative supply of cooking jars are traced and different trade routes to and within the three micro-regions are proposed.